Margaret Storm Jameson and the Spanish Civil War : The Fight for Human Values - Birkett, Jennifer (Journal of English Studies, 2008)
Spain is not generally thought of as a significant theme in Jameson’s writing, or her political formation. But careful study of her life and writing discloses numerous connections to the country from the early 1930s onwards, and No Victory for the Soldier (1938), the novel she published under the pseudonym of James Hill, in the 1930s, closes with a lengthy section on the Spanish Civil War. The tragic heroism of the Republic at war provides the ideal context for Jameson’s exploration of the capacity of modernist art, or rather, modernist artists (the Auden generation) to speak in the name of the future of the common man. Spain, and especially the Basque country, fighting the fascist war machine, is one of the last repositories of humane living and European values: reason, justice, humanity and decency.